Verdi's Otello - Boito, Arrigo, 1842-1918 (Opera classics library., 2005)
A comprehensive guide to Verdi's OTELLO, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English translation side-by side, and over 30 music highlight examples.